2015
DOI: 10.1177/1060028015606469
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prenatal Acetaminophen Exposure and Future Risk of Attention Deficit/Hyperactivity Disorder in Children

Abstract: While there does appear to be a mild correlation between prenatal acetaminophen use and the development of ADHD symptoms in children, current data do not provide sufficient evidence that prenatal acetaminophen exposure leads to development of ADHD symptoms late in life. Acetaminophen is a preferred option for pain management during pregnancy when compared with other medications such as nonsteroidal anti-inflammatory drugs or opioids for pyretic or pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…1 It has been previously reported that between 40% and 65% of pregnant women use acetaminophen, [1][2][3][4][5][6][7] with estimates of 3%-20% of women reporting use in all three trimesters. 3,8 An emerging set of studies have signalled modest, yet concerning associations between acetaminophen and select pregnancy and childhood adverse outcomes, including preeclampsia, 9,10 preterm birth, 9 asthma (review and meta-analysis 11 ), and neurodevelopmental disorders [3][4][5][6][7][8][12][13][14] (review and meta-analysis 15 ). However, interpretation of these findings as causally related to prenatal acetaminophen exposure has been problematic.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…1 It has been previously reported that between 40% and 65% of pregnant women use acetaminophen, [1][2][3][4][5][6][7] with estimates of 3%-20% of women reporting use in all three trimesters. 3,8 An emerging set of studies have signalled modest, yet concerning associations between acetaminophen and select pregnancy and childhood adverse outcomes, including preeclampsia, 9,10 preterm birth, 9 asthma (review and meta-analysis 11 ), and neurodevelopmental disorders [3][4][5][6][7][8][12][13][14] (review and meta-analysis 15 ). However, interpretation of these findings as causally related to prenatal acetaminophen exposure has been problematic.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The most common uses are for headache and fever. 2 Acetaminophen crosses the placenta relatively easily and has been reported in umbilical cord blood after maternal administration in labor. 3 While largely considered to be safe during pregnancy, a few recently published observational studies have reported an association between prenatal acetaminophen use and potential increased risk for adverse neurological outcomes in childhood.…”
mentioning
confidence: 99%
“…10 Two systematic reviews of the existing studies have both determined that evidence is insufficient to conclude that there is an association between maternal acetaminophen use and ADHD in offspring. 2,11 While correlating exposures during pregnancy with childhood outcomes is problematic, it is especially difficult with regard to neurobehavioral disorders. The definition and diagnosis of these illnesses, especially ADHD, continues to evolve.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 In contrast, it is not commonly known that acetaminophen (paracetamol), a medication that is available over the counter in most countries and that is widely regarded as a safe drug for use during pregnancy, 2,3 has also been associated with neuropsychiatric risks, with neurodevelopmental delay, 4 ASD, 5 and even attention-deficit/hyperactivity disorder (ADHD) 6 described as possible consequences of prenatal use. This article examines the possible association between prenatal use of acetaminophen and ASD in the offspring.…”
Section: Introductionmentioning
confidence: 99%